Portrait of Multiliteracy Learning in Elementary Schoool Students - Imran, Muh Erwinto; Sopandi, Wahyu; Azwan, Diana Putri (International Conference on Elementary Education, 2020)
This study aimed to describe the portrait of multiliteracy learning in elementary school students in the Bandung. The research data were obtained from giving questionnaires, interviews, and observation. The urgency of this research was the evaluation of teacher competence in planning, implementing and evaluating learning. The results showed about learning preparation that was found in the high category, learning implementation that was found in the medium category, the assessment that was found in the very high category, and professional development that was found in the low category. The results of observations of teacher and student activities that occurred during the learning process showed multiliteracy activities. The researcher obtained read and write literacy activities at 60%, numeracy literacy at 50%, scientific literacy at 40%, cultural literacy at 40%, technology literacy at 20%, and communication literacy at 20%. These results indicated that multiliteracy learning was still lacking, and it needs to be improved